Modified Descemet’s Stripping Automated Endothelial Keratoplasty: The Use of Ophthalmic Viscoelastic Devices in Hypotonic Eyes That Had Undergone Glaucoma Filtering Surgeries - Itaru Oyakawa; Takahiko Hayashi; Toshiki Shimizu; Naoko Kato (Case Reports in Ophthalmological Medicine)
Purpose. Descemet’s stripping automated endothelial keratoplasty (DSAEK) is more difficult in hypotonic eyes with filtering bleb, due to the difficulties in elevating the intraocular pressure (IOP). We report a new method that uses ophthalmic viscoelastic devices (OVDs) to achieve good graft adhesion. Case Presentation. We performed modified DSAEK surgery on 2 eyes of 2 patients, who had previously undergone a trabeculectomy. Both eyes had functioning filtering blebs; the IOP was lower than 10 mmHg without medication. After the graft was inserted into the anterior chamber, the conjunctiva was penetrated, apart from the bleb, using a 30 G needle, and Healon V® was injected into the bleb until the encapsulated space was filled completely. Air was subsequently injected into the anterior chamber to promote the graft attachment to the back surface of the cornea. The IOP was elevated above 40 mmHg in both eyes 1 h after surgery and then decreased to less than 30 mmHg over the subsequent 3 h period. The implanted graft showed good adhesion and no dislocation. Conclusions. Our novel DSAEK procedure that adds one step of OVD injection into the filtering bleb may be useful for hypotonic eyes that had undergone filtering surgeries.